Leaf endophytic fungi of chili (Capsicum annuum) and their role in the protection against Aphis gossypii (Homoptera: Aphididae) - HENY HERNAWATI; SURYO WIYONO; SUGENG SANTOSO (Biodiversitas Journal of Biological Diversity, 2011)
Hernawati H, Wiyono S, Santoso S (2011) Leaf endophytic fungi of chili (Capsicum annuum) and their role in the protection against Aphis gossypii (Homoptera: Aphididae). Biodiversitas 12: 187-191. The objectives of the research were to study the diversity of leaf endophytic fungi of chili, and investigate its potency in protecting host plants against Aphis gossypii Glov. Endophytic fungi were isolated from chili leaves with two categories: aphid infested plants and aphid-free plants, collected from farmer’s field in Bogor, West Java. Abundance of each fungal species from leave samples was determined by calculating frequency of isolation. The isolated fungi were tested on population growth of A. gossypii. The fungal isolates showed suppressing effect in population growth test, was further tested on biology attributes i.e. life cycle, fecundity and body length. Five species of leaf endophytic fungi of chili were found i.e.Aspergillus flavus, Nigrospora sp., Coniothyrium sp., and SH1 (sterile hypha 1), SH2 (sterile hypha 2). Even though the number of endophytic fungi species in aphid-free and aphid-infested plant was same, the abundance of each species was different. Nigrospora sp., sterile hyphae 1 and sterile hyphae 2 was more abundant in aphid-free plants, but there was no difference in dominance of Aspergillus flavus and Coniothyrium sp. Nigrospora sp., SH1 and SH2 treatment reduced significantly fecundity of A. gossypii. Only SH2 treatment significantly prolonged life cycle and suppress body length, therefore the fungus had the strongest suppressing effect on populationgrowth among fungi tested. The abundance and dominance of endophytic fungal species has relation with the infestation of A. gossypii in the field.